Techno-Economic Assessment of Smart Photovoltaic-Water Infrastructure Development for a Residential Community in Peri-Urban Ikorodu, Lagos State, Nigeria - Ibikunle Ogundari; Oladimeji BAKARE; Olaleye SALU (Journal of Digital Food, Energy & Water Systems)
Potable water demand in peri-urban Lagos State has necessitated the development of strategic combined power and water infrastructure. The techno-economic viability assessment of a smart photovoltaic-water treatment system in peri-urban Ikorodu, Lagos State was effected as an extenuation approach to pervasive insufficient potable water provision under the State’s integrated clean water initiatives. An energy technology foresight analysis methodology was used. The study determined an appropriate infrastructural option – a combined 180 kW smart PV, 400 m3/day smart water treatment system requiring 0.65 acres of land, and generating annually 146,000 litres of potable water. The smart PV-water plant initiative was considered to have acceptable risk (Payback period between 16.29 to 18.41 years; Return on Investment = 5.43%) and viability at the minimum water price of $ 2.08/m3. It also had costs savings of $ 73,000/year relative to the water vendor supply option. The study recommended a reduction in plant operating costs to improve the viability of the smart PV-water treatment system. The study concluded that the smart PV-water treatment system project was technologically attainable, economically viable and eco-friendly, and consequently recommended its establishment in the study area.